2013
DOI: 10.1016/j.carbpol.2013.02.044
|View full text |Cite
|
Sign up to set email alerts
|

High stability of immobilized β-d-galactosidase for lactose hydrolysis and galactooligosaccharides synthesis

Abstract: β-D-Galactosidase from Kluyveromyces lactis was immobilized on glutaraldehyde-activated chitosan and used in a packed-bed reactor for the continuous hydrolysis of lactose and the synthesis of galactooligosaccharides (GOS). The biocatalyst was tested for its optima pH and temperature, thermal stability in the presence of substrate and products, and operational stability. Immobilization increased the range of operational pH and temperature, and the enzyme thermal stability was sharply increased in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 38 publications
3
48
0
2
Order By: Relevance
“…Kluyveromyces lactis [12] and Kluyveromyces fragilis [13], having the advantage of non-toxicity 13 and biocompatibility. Multi-walled carbon nanotubes were also functionalized with 14 glutaraldehyde in order to increase the bound enzyme amount [14].…”
mentioning
confidence: 99%
“…Kluyveromyces lactis [12] and Kluyveromyces fragilis [13], having the advantage of non-toxicity 13 and biocompatibility. Multi-walled carbon nanotubes were also functionalized with 14 glutaraldehyde in order to increase the bound enzyme amount [14].…”
mentioning
confidence: 99%
“…Particularly, Verma et al, showed that the thermal stability of lipase was greatly improved upon its immobilization onto carbon nanotubes (89), while Klein and coworkers showed a similar phenomenon for β-D-Galactosidase immobilized onto chitosan (90). Further, affinity immobilization was shown to exploit the specificity of the enzyme to the substrate, in different physiological conditions, to increase enzyme immobilization capacity and reusability (91).…”
Section: Enzymes For Wastewater Treatmentmentioning
confidence: 91%
“…It was noted that soluble β-galactosidase showed 41 % activity at 70 °C, whereas the immobilized β-galactosidase retained 67 % activity at the same temperature. Immobilization also resulted in improved stability of immobilized β-galactosidase for glutaraldehyde-activated chitosan (Klein et al, 2013). The probable reason for this may be that covalent binding and crosslinking provided a more rigid external backbone for β-galactosidase immobilization.…”
Section: Eff Ect Of Ph and Temperaturementioning
confidence: 97%